Effect of fruit juices and pomace extracts on the growth of Gram-positive and Gram-negative bacteria - Krisch, Judit (Acta Biologica Szegediensis, 2008)
Extracts and juices of cultivated and wild fruits belonging to the families Rosaceae, Grossulariaceae, Moraceae, Berberidaceae, Polygonaceae, Caprifoliaceae and Cornaceae were examined for their growth reducing activity on four bacteria (Bacillus subtilis, B. cereus var. mycoides, Escherichia coli and Serratia marcescens). In vitro antibacterial activities were evaluated by microdilution plate assays. Black currant (Ribes nigrum), cornelian cherry (Cornus mas) and European rowan (Sorbus aucuparia) had the highest growth inhibition capacity.